2017
DOI: 10.1590/1807-3107bor-2017.vol31.0045
|View full text |Cite
|
Sign up to set email alerts
|

The anti-caries activity and toxicity of an experimental propolis-containing varnish

Abstract: Abstract:We investigated the anti-caries effects of an experimental propolis varnish in vivo, and further tested its toxicity against fibroblasts. Fifty-six SPF female Wistar rats were infected with Streptococcus mutans UA159 (SM) and allocated into four groups (n = 14/group): G1, propolis varnish (15%/PV); G2, chitosan varnish (CV/vehicle); G3, gold standard (GS/Duraphat ® ); and G4, untreated. The animals received a single varnish application on their molars and were submitted to a high cariogenic challenge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 36 publications
1
20
0
2
Order By: Relevance
“…They are composed of polymer matrices, excipients and the active principle. In the case of the present varnish the chosen matrix was insoluble, in this case ethylcellulose, used to modulate the release of the active principle and thus the substantivity was higher (De Luca et al, 2017). This type of formulation adheres to dental fissures and scars, gradually releasing the active principle, thus becoming a long-term therapeutic agent suitable for antimicrobial formulation (Franca et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…They are composed of polymer matrices, excipients and the active principle. In the case of the present varnish the chosen matrix was insoluble, in this case ethylcellulose, used to modulate the release of the active principle and thus the substantivity was higher (De Luca et al, 2017). This type of formulation adheres to dental fissures and scars, gradually releasing the active principle, thus becoming a long-term therapeutic agent suitable for antimicrobial formulation (Franca et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The pretreatment did not exhibit a complete gain of the surface hardness but was able to minimize its reduction as well as performed when APF was used solely. Researchers and clinicians still need to search for approaches for enamel remineralization that could be effective with prolonged remineralization effect, exploring natural agents or conciliating available methods [19,27]. It still is necessary to stablish that the different advances can serve for different population, regarding preventive and/ or early treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The new tissues formed inside the root canal showed characteristics similar to the cementum, bone, and periodontal ligament 14 Valones et al [24] The present study demonstrated that a dentifrice containing exclusively rosemary extract has the capability of inhibiting the growth of the studied bacteria. However, for the inhibition of L. rhamnosus, a propolis-based commercial dentifrice was more effective than the dentifrice containing rosemary extract 15 De Luca et al [25] All rats gained weight and remained apparently healthy and active throughout the experiment. The PV (typ.…”
Section: N°bibliographic Referencementioning
confidence: 98%
“…The inorganic components are formed by minerals (quartz, kaolinite, illite, and gibbsite), identified by X-ray diffraction and infrared spectroscopy, which are common in the soil of the region. The analyses by X-ray fluorescence indicate that the most common oxides are SiO2, Al2O3, and Fe2O3 within minerals 25 Silva et al [35] Twenty-two pollen types were identified. The total phenolic content ranged from 17 to 66 mg GAE/g of extract; the highest contents were found in honeys produced from pollen types such as Clidemia and Myrcia.…”
Section: N°bibliographic Referencementioning
confidence: 99%